THREE MAIN PROBLEMS IN THE IMPLEMENTATION OF NATIONAL HEALTH INSURANCE CAUSE A DEFICIT OF SOLUTIONS THAT NEED TO BE DONE IMMEDIATELY - Ellen Manik (Sean Institute, 2023)
National Health Insurance (JKN) is part of the National Social Security System (SJSN) organized by the Social Security Organizing Agency (BPJS) Health through a compulsory social health insurance mechanism. Every JKN participant has the right to obtain comprehensive health services that are tiered, effective, and efficient by applying the principles of quality control and cost control based on medical indications. The deficit in Health Social Security funds or BPJS Kesehatan is a mismatch between the suboptimal income sourced from participant contributions and the large burden of health insurance that needs to be borne. However, in this situation, there are still several main problems in implementing national health insurance that cause deficits that must be done immediately. The author formulates the problem in this study: How is the government's solution to the deficit of the National Health Insurance Fund. The research method used by the author in this study is Normative Juridical. Conclusion It is necessary to establish a strong mechanism to make participants pay contributions continuously. This can be done by making arrangements to use BPJS for public services. If someone does not actively pay their BPJS, they cannot enjoy public facilities provided by the government. Then, the next solution is to increase the supervision team to oversee the performance of hospitals that provide BPJS services.